The KPZ Equation and Moments of Random Matrices - Gorin, Vadim; Sodin, Sasha (Журнал математической физики, анализа, геометрии, 2018)
The logarithm of the diagonal matrix element of a high power of a random matrix converges to the Cole–Hopf solution of the Kardar–Parisi–Zhang equation in the sense of one-point distributions. Логарифм дiагонального матричного елемента високого ступеня випадкової матрицi збiгається до розв язку Коле Гопфа рiвняння Кардара Парiсi Жанга в сенсi одноточкових розташувань.